Prior entry and temporal attention: Cueing affects order errors in RSVP. - Hilkenmeier, Frederic; Olivers, Christian N. L.; Scharlau, Ingrid (Journal of Experimental Psychology: Human Perception and Performance)
The law of prior entry states that attended objects come to consciousness more quickly than unattended ones. This has been well established in spatial cueing paradigms, where two task-relevant stimuli are presented near-simultaneously at two different locations. Here, we suggest that prior entry also plays a pivotal role in temporal attention paradigms, where stimuli appear at the same location but at distinct moments in time, in rapid serial presentation (RSVP). Specifically, we hypothesize that prior entry can explain temporal order reversals in reporting two targets from RSVP. In support of this, three experiments show that cueing attention toward either of the targets has a strong influence on order errors. We conclude that prior entry provides a viable explanation of the way in which relevant information is prioritized in RSVP. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: attentional blink; attentional enhancement; lag-1 sparing; prior entry; temporal cueing; visual attention; rapid serial presentation; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Female; Humans; Male; Neuropsychological Tests; Pattern Recognition; Visual; Time Factors; Visual Perception; Young Adult; Cues; Serial Recall; Visual Attention; Eyeblink Reflex

At the mercy of prior entry: Prior entry induced by invisible primes is not susceptible to current intentions. - Weiß, Katharina; Scharlau, Ingrid (Acta Psychologica)
If one of two events is attended to, it will be perceived earlier than a simultaneously occurring unattended event. Since 150 years, this effect has been ascribed to the facilitating influence of attention, also known as prior entry. Yet, the attentional origin of prior-entry effects¹ has been repeatedly doubted. One criticism is that prior-entry effects might be due to biased decision processes that would mimic a temporal advantage for attended stimuli. Although most obvious biases have already been excluded experimentally (e.g. judgment criteria, response compatibility) and prior-entry effects have shown to persist (Shore, Spence, & Klein, 2001), many other biases are conceivable, which makes it difficult to put the debate to an end. Thus, we approach this problem the other way around by asking whether prior-entry effects can be biased voluntarily. Observers were informed about prior entry and instructed to reduce it as far as possible. For this aim they received continuous feedback
Keywords: intentions; events; attention; decision processes; Adult; Attention; Choice Behavior; Cues; Female; Humans; Intention; Judgment; Male; Middle Aged; Reaction Time; Time Perception; Visual Perception; Attention; Decision Making; Experiences (Events); Intention

Prior entry explains order reversals in the attentional blink. - Olivers, Christian N. L.; Hilkenmeier, Frederic; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
When two targets are presented in rapid succession, the first target (T1) is usually identified, but the second target (T2) is often missed. A remarkable exception to this 'attentional blink' occurs when T2 immediately follows the first T1, at lag 1. It is then often spared but reported in the wrong order—that is, before T1. These order reversals have led to the hypothesis that 'lag 1 sparing' occurs because the two targets merge into a single episodic representation. Here, we report evidence consistent with an alternative theory: T2 receives more attention than T1, leading to prior entry into working memory. Two experiments showed that the more T2 performance exceeded that for T1, the more order reversals were made. Furthermore, precuing T1 led to a shift in performance benefits from T2 to T1 and to an equivalent reduction in order reversals. We conclude that it is not necessary to assume episodic integration to explain lag 1 sparing or the accompanying order reversals. (PsycINFO Dat
Keywords: attentional blink; order reversals; prior entry; working memory; visual attention; attentional performance; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Discrimination (Psychology); Female; Humans; Male; Memory; Short-Term; Pattern Recognition; Visual; Psychophysics; Reaction Time; Reversal Learning; Sensory Gating; Serial Learning; Young Adult; Eyeblink Reflex; Stimulus Change; Stimulus Parameters; Visual Attention; Attentional Blink; Short Term Memory

Simultaneity and temporal order perception: Different sides of the same coin? Evidence from a visual prior-entry study. - Weiß, Katharina; Scharlau, Ingrid (The Quarterly Journal of Experimental Psychology)
Attended stimuli are perceived as occurring earlier than unattended stimuli. This phenomenon of prior entry is usually identified by a shift in the point of subjective simultaneity (PSS) in temporal order judgements (TOJs). According to its traditional psychophysical interpretation, the PSS coincides with the perception of simultaneity. This assumption is, however, questionable. Technically, the PSS represents the temporal interval between two stimuli at which the two alternative TOJs are equally likely. Thus it also seems possible that observers perceive not simultaneity, but uncertainty of temporal order. This possibility is supported by prior-entry studies, which find that perception of simultaneity is not very likely at the PSS. The present study tested the percept at the PSS in prior entry, using peripheral cues to orient attention. We found that manipulating attention caused varying temporal perceptions around the PSS. On some occasions observers perceived the two stimuli as sim
Keywords: temporal order perception; simultaneity; temporal order judgment; attention; visual perception; Adolescent; Adult; Attention; Cues; Discrimination (Psychology); Female; Humans; Judgment; Male; Models; Psychological; Photic Stimulation; Reaction Time; Time Factors; Uncertainty; Visual Perception; Young Adult; Attention; Judgment; Stimulus Similarity; Time Perception; Visual Discrimination; Temporal Order (Judgment)

Enhancing implicit change detection through action. - Tseng, Philip; Tuennermann, Jan; Roker-Knight, Nancy; Winter, Dorina; Scharlau, Ingrid; Bridgeman, Bruce (Perception)
Implicit change detection demonstrates how the visual system can benefit from stored information that is not immediately available to conscious awareness. We investigated the role of motor action in this context. In the first two experiments, using a one-shot implicit change detection paradigm, participants responded to unperceived changes either with an action (jabbing the screen at the guessed location of a change) or with words (verbal report), and sat either 60 cm or 300 cm (with a laser pointer) away from the display. Our observers guessed the locations of changes at a reachable distance better with an action than with a verbal judgment. At 300 cm, beyond reach, the motor advantage disappeared. In experiment 3, this advantage was also unavailable when participants sat at a reachable distance but responded with hand-held laser pointers near their bodies. We conclude that a motor system specialized for real-time visually guided behavior has access to additional visual information.
Keywords: implicit change detection; action perception; visual system; perceptual judgment; verbal fluency; Analysis of Variance; Awareness; Female; Humans; Male; Psychomotor Performance; Random Allocation; Reaction Time; Visual Perception; Visual Memory; Visual Stimulation; Implicit Memory; Judgment; Perceptual Discrimination

Latency facilitation in temporal-order judgments: Time course of facilitation as a function of judgment type. - Scharlau, Ingrid; Ansorge, Ulrich; Horstmann, Gernot (Acta Psychologica)
The paper is concerned with two models of early visual processing which predict that priming of a visual mask by a preceding masked stimulus speeds up conscious perception of the mask (perceptual latency priming). One model ascribes this speed-up to facilitation by visuo-spatial attention [Scharlau, I., & Neumann, O. (2003a). Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional explanation. Psychological Research 67, 184-197], the other attributes it to nonspecific upgrading mediated by retino-thalamic and thalamo-cortical pathways [Bachmann, T. (1994). Psychophysiology of visual masking: The fine structure of conscious experience. Commack, NY: Nova Science Publishers]. The models make different predictions about the time course of perceptual latency priming. Four experiments test these predictions. The results provide more support for the attentional than for the upgrading model. The experiments further demonstrate that testing latency facilitation w
Keywords: latency facilitation; temporal order judgments; visual processing; priming; conscious perception; visual mask; Adult; Attention; Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Space Perception; Time Perception; Visual Perception; Consciousness States; Judgment; Priming; Visual Masking; Temporal Order (Judgment)

More efficient rejection of happy than of angry face distractors in visual search. - Horstmann, Gernot; Scharlau, Ingrid; Ansorge, Ulrich (Psychonomic Bulletin & Review)
In the present study, we examined whether the detection advantage for negative-face targets in crowds of positive-face distractors over positive-face targets in crowds of negative faces can be explained by differentially efficient distractor rejection. Search Condition A demonstrated more efficient distractor rejection with negative-face targets in positive-face crowds than vice versa. Search Condition B showed that target identity alone is not sufficient to account for this effect, because there was no difference in processing efficiency for positive- and negative-face targets within neutral crowds. Search Condition C showed differentially efficient processing with neutral-face targets among positive- or negative-face distractors. These results were obtained with both a within-participants (Experiment 1) and a between-participants (Experiment 2) design. The pattern of results is consistent with the assumption that efficient rejection of positive (more homogenous) distractors is an im
Keywords: angry face distractors; visual search; negative face distractors; Adult; Anger; Attention; Face; Female; Happiness; Humans; Male; Rejection (Psychology); Visual Perception; Distraction; Face Perception; Visual Perception; Visual Search

Visual search for a motion singleton among coherently moving distractors. - Ansorge, Ulrich; Scharlau, Ingrid; Labudda, Kirsten (Psychological Research)
In the current study, we tested whether search for a visual motion singleton presented among several coherently moving distractors can be more efficient than search for a motion stimulus presented with a single distractor. Under a variety of conditions, multiple spatially distributed and coherently moving distractors facilitated search for a uniquely moving target relative to a single-motion-distractor condition (Experiments 1,3, and 4). Color coherencies among static distractors were not equally effective (Experiments 1 and 2). These results confirm that humans are highly sensitive to antagonistically directed motion signals in backgrounds compared with spatially more confined regions of visual images. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual search; motion singleton; visual images; visual motion; coherently moving distractors; Adult; Attention; Exploratory Behavior; Female; Humans; Male; Motion Perception; Visual Perception; Motion Perception; Stimulus Salience; Visual Search; Distraction; Retinal Image

Evidence for split foci of attention in a priming paradigm. - Scharlau, Ingrid (Perception & Psychophysics)
Most models of visuospatial attention include the notion that attention is dedicated to a single location in space. However, several researchers have found evidence that under appropriate circumstances, attention may be allocated to noncontiguous locations (e.g., Awn & Pashler, 2000; Bichot, Cave, & Pashler, 1999; Kramer & Hahn, 1995). In the present experiments, the spatial distribution of attention was assessed by a novel method, perceptual latency priming: the latency benefit of an attended visual stimulus, as compared with a nonattended stimulus. Experiment 1 assessed whether observers are able to attend to two nonadjacent regions or a region of variable size. Experiment 2 tested whether, when two distant locations are attended to, the region between them is necessarily also in the focus of attention. Two further experiments controlled for objections against the method used and replicated the main results of the first two experiments. The experiments showed a robust attentional pr
Keywords: visuospatial attention; priming paradigm; spatial distribution; Adult; Attention; Female; Humans; Male; Attention; Priming; Spatial Perception; Visuospatial Ability

Evidence against response bias in temporal order tasks with attention manipulation by masked primes. - Scharlau, Ingrid (Psychological Research)
Attending to a location shortens the perceptual latency of stimuli appearing at this location (perceptual latency priming). According to attentional explanations, perceptual latency priming relies on the speeded transfer of attended visual information into an internal model. However, doubts about the attentional origin have repeatedly been raised because efforts to minimize response bias have been insufficient in most studies. Five experiments investigated the contribution of a response bias to perceptual latency priming (judgment bias due to the two-alternative forced-choice method and due to the existence of the prime, criterion effects or second-order bias, sensorimotor priming). If any, only small response biases were found. The results thus support the attentional explanation. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: response bias; temporal order tasks; attention manipulation; masked primes; perceptual latency priming; Adult; Attention; Discrimination Learning; Female; Humans; Male; Memory; Short-Term; Orientation; Pattern Recognition; Visual; Perceptual Masking; Psychomotor Performance; Psychophysics; Reaction Time; Serial Learning; Attention; Latent Learning; Priming; Response Bias; Visual Perception; Response Latency; Temporal Order (Judgment)

Direct parameter specification of an attention shift: Evidence from perceptual latency priming. - Scharlau, Ingrid; Ansorge, Ulrich (Vision Research)
In the direct parameter specification (DPS) mode of sensorimotor control, response parameters can be specified by stimuli that are not consciously perceived [Psychological Research/Psychologische Forschung 52 (1990) 207]. DPS is contingent on the current intentions. The invisible stimuli can be processed for the purposes of sensorimotor control only if they match the actual intentions, for example, share task-relevant features. The present experiments explore whether attentional capture by masked abrupt-onset stimuli is mediated via DPS. Participants judged which of two visual targets appeared first. Masked primes preceded one of the targets. The primes were either similar to the targets or not, in shape, or in color. Target-like (task-relevant), but not distractor-like (task-irrelevant), primes facilitated perceptual latencies of targets trailing at their positions. Thus, the latency effects resulted from DPS of an attention shift, rather than from bottom-up capture or from top-down
Keywords: direct parameter specification; DPS; attention shift; latency priming; sensorimotor control; stimuli; task-relevant features; visual targets; color; shape; latency effects; Adult; Attention; Discrimination (Psychology); Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Visual Perception; Attention; Perceptual Motor Processes; Response Latency; Stimulus Onset; Visual Stimulation; Form and Shape Perception; Sensory Adaptation

Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional interpretation. - Scharlau, Ingrid; Neumann, Odmar (Psychological Research)
Four experiments investigated the influence of a metacontrast-masked prime on temporal order judgments. The main results were (1) that a masked prime reduced the latency of the mask's conscious perception (perceptual latency priming), (2) that this effect was independent of whether the prime suffered strong or weak masking, (3) that it was unaffected by the degree of visual similarity between the prime and the mask, and that (4) there was no difference between congruent and incongruent primes. Finding (1) suggests that location cueing affects not only response times but also the latency of conscious perception. (2) The finding that priming was unaffected by the prime's detectability argues against a response bias interpretation of this effect. (3) Since visual similarity had no effect on the prime's efficiency, it is unlikely that sensory priming was involved. (4) The lack of a divergence between the effects of congruent and incongruent primes implies a functional difference between t
Keywords: perceptual latency priming; temporal order judgments; masked stimuli; unmasked stimuli; attentional interpretation; response times; location cueing; visual perception; Adult; Attention; Female; Humans; Male; Models; Psychological; Perceptual Masking; Psychometrics; Reaction Time; Task Performance and Analysis; Time Perception; Masking; Reaction Time; Response Latency; Stimulus Parameters; Visual Contrast; Attention; Cues; Priming; Temporal Frequency; Temporal Order (Judgment)

Temporal parameters and time course of perceptual latency priming. - Scharlau, Ingrid; Neumann, Odmar (Acta Psychologica)
Visual stimuli (primes) reduce the perceptual latency of a target appearing at the same location (perceptual latency priming, PLP). Three experiments assessed the time course of PLP by masked and, in Experiment 3, unmasked primes. Experiments 1 (N=11; mean age 26.9) and 2 (N=12; mean age 25.6) investigated the temporal parameters that determine the size of priming. Stimulus onset asynchrony was found to exert the main influence accompanied by a small effect of prime duration. Experiment 3 (N=19; mean age 27.7) used a large range of priming onset asynchronies. We suggest to explain PLP by the Asynchronous Updating Model which relates it to the asynchrony of 2 central coding processes, preattentive coding of basic visual features and attentional orienting as a prerequisite for perceptual judgments and conscious perception. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Keywords: perceptual latency priming; temporal parameters; Asynchronous Updating Model; time course; stimulus onset asynchrony; visual masking; attention; Adult; Attention; Female; Humans; Male; Perceptual Masking; Reaction Time; Time Perception; Visual Perception; Attention; Priming; Stimulus Onset; Visual Masking; Visual Perception; Models; Time

Influences of visibility, intentions, and probability in a peripheral cuing task. - Ansorge, Ulrich; Heumann, Manfred; Scharlau, Ingrid (Consciousness and Cognition: An International Journal)
According to the concept of direct parameter specification, nonconsciously registered information can be processed to the extent that it matches currently active intentions of a person. This prediction was tested and confirmed in the current study. Masked visual information provided by peripheral cues led to reaction time (RT) effects only if the information specified one of the required responses (Experiments 1 and 3). Information delivered by the same masked cues that did not match the intentions was not used. However, the same information influenced RT if it was provided by visible cues (Experiments 2 and 3). The results suggest that the processing of nonconsciously registered information is flexible because it is susceptible to the changing intentions of a person. Yet, these processes are apparently restricted as nonconsciously registered information cannot be used as easily for purposes not corresponding to the currently active intentions as better visible information. (PsycINFO
Keywords: active intentions; cues; direct parameter specification; nonconscious processing ability; Adult; Consciousness; Female; Humans; Male; Mental Processes; Perceptual Masking; Photic Stimulation; Visual Perception; Awareness; Cognitive Processes; Cues; Intention; Consciousness States; Probability

Leading, but not trailing, primes influence temporal order perception: Further evidence for an attentional account of perceptual latency priming. - Scharlau, Ingrid (Perception & Psychophysics)
Presenting a masked prime leading a target influences the perceived onset of the masking target. This priming effect is explained by the asynchronous updating model: The prime initiates attentional allocation toward its location, which renders a trailing target at the same place consciously available earlier. In 3 experiments, this perceptual latency priming by leading primes was examined jointly with the effects of trailing primes in order to compare the explanation of the asynchronous updating model with the onset-averaging and the P-center hypotheses. Exp 1 (n=15, mean age 27.1 yrs) showed that an attended, as well as an unattended, prime leads to perceptual latency priming. In addition, a large effect of trailing primes on the onset of a target was found. As Exp 2 (n=13, mean age 26.5 yrs) demonstrated, this effect is quite robust, although smaller than that of a leading prime. In Exp 3 (n=13, mean age 24.8 yrs), masked primes were used. Under these conditions, no influence of tra
Keywords: attention; leading primes; trailing primes; temporal order perception; perceptual latency priming; Adult; Attention; Female; Fixation; Ocular; Humans; Male; Perceptual Masking; Random Allocation; Time Perception; Visual Perception; Attention; Masking; Priming; Stimulus Frequency; Temporal Frequency; Temporal Order (Judgment)